An efficient thin layer equivalent technique of SETD method for thermo-mechanical multi-physics analysis of electronic devices. (15th August 2022) - Liu, Qi Qiang; Zhuang, Mingwei; Zhan, Weichen; Liu, Na; Liu, Qing Huo
Highlights: Assessments by means of a scoring system in public tender procedures are studied. Assessments are the composition of two steps: 1st-partial scores, 2nd-global scores. Partial scores are upper bounded by an exogenous threshold or cap. Weighted means of the attribute assessments satisfy reasonable properties. Truncation avoids the exclusion paradox. Abstract: A coupled thermo-mechanical simulation technique is proposed for reliability analyses of electronic devices based on the spectral element time domain (SETD) method. The transient spatial distribution of temperature, deformation and stress in electronic devices with different spatial scales can be obtained by using the implicit time integration method in the proposed technique. Through the thermo-mechanical equations, thin layers of electronic devices in the coupled fields can be made equivalent to surface boundaries to avoid volumetric meshing, thus reducing the number of degrees of freedom in computation and greatly improving the numerical efficiency of reliability analyses. Finally, through the thermo-mechanical analyses of different electronic devices such as a coaxial through-silicon via (TSV), and an integrated circuit (IC) package, various stress mechanisms related to the failure of electronic devices are successfully predicted to further demonstrate the capabilities of the technique to analyze the reliability of large-scale electronic devices.